EVALUASI PENYUSUNAN LAPORAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH: PADA DIREKTORAT JENDERAL MINYAK DAN GAS BUMI - , ELFRIDA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The effort in achieving good governance is focused on a performance evaluation as a responsibility to public. This kind of concept is known as New Public Management. This concept is more oriented on input, activity, output, and outcome which emphasize more on performance achievement. The tools to evaluate performance is required to identify performance achievement. One of them is the logic model. This model is considered as an effective method in planning and evaluating programs This research attempts to evaluate the performance of Directorate General of Oil and Gas by using tools such as the logic model and performance blue print to assess the quality of performance indicators which is planned based on its planning and reporting documents. The result of this research has pointed up many contradictions and discrepancies between strategical targets, performance indicators, and service-delivery outcome basis within the performance of Directorate General of Oil and Gas. Keyword: new public management, logic model, performance blueprint, four quadrant analysys, OPM&M, The Evaluated Planning of Government Institution Accountability and Performance Report